The Omani Mosques and the Mosque Unearthed by the Italian Archaeological Mission at Ẓafār/al-Balīd, in the Dhofar Region - Giunta, Roberta (Annali dell'Istituto Universitario Orientale di Napoli, 2024)
Abstract The article provides a brief overview of the Omani mosques that the Italian archaeologist P.M. Costa classified into two groups in the 1970s based on their floor plans, architectural features, and decorative elements: those from the northern inland regions and those situated along the Indian Ocean coast. A new mosque recently brought to light by the Italian Archaeological Mission to al-Balīd of the University of Naples L’Orientale belongs to this second group.
Keywords: Architecture -- Oman; Archéologie -- Oman

‘Architectural Design for Procuring Thermal Comfort’: Hassan Fathy, Nubia, and Desert Building - Reynolds, Nancy Y. (International Journal of Islamic Architecture, 2024)
As part of an indigenous building movement in the Global South, the United Nations published two books by Egyptian architect Hassan Fathy (1900–89): one on building ‘for the poor’ and the other on passive cooling in vernacular architecture from hot environments. Using his correspondence, reports, designs, published writings, and built forms, this article tracks Fathy’s changing use of a crucial technique, mud-brick vaulting, that he learned in Nubia, an area of Egypt’s arid south largely destroyed by dams in the twentieth century. I show how Fathy mined Nubia rhetorically and materially to use, and later attempt to copyright, its residents’ ‘instinctive’ skills for living in hot arid lands. Over time, Fathy’s appropriations helped to transform Nubia’s vernacular morphology into a universal commons of desert and ‘Islamic’ forms, which enabled him to expand the geographic scope of his practice into the Arabian Peninsula in Oman and Saudi Arabia and into the southwestern United States.
Keywords: Architecture -- Oman

Mutrah Old Market, Oman: Analysis to Enhance a Living Heritage Site - Amer, Mohamed (Tangible and Intangible Heritage in the Age of Globalisation, 2024)
Mohamed Amer examines the tangible and intangible heritage characteristics of the traditional market of Mutrah in Oman’s capital city of Muscat. He assesses its interactive historic, architectural, urban, social, economic and cultural values alongside their managerial features, in order to identify practical measures for the enhancement of this living cultural heritage, the effective preservation of Omani cultural identity, avenues for local socio-economic empowerment and sustainable cultural tourism. Here, Strengths, Weaknesses, Opportunities and Threats (SWOT) analyses brought to light the internal and external factors that are favourable to achieving these objectives.
Keywords: Architecture -- Oman

The built heritage as a resource for architectural education: documentation of the vernacular settlements and architecture in Oman - Benkari, Naïma (Journal of Cultural Heritage Management and Sustainable Development, 2024)
Keywords: Architecture -- Oman